Listening to motivational music during warming-up attenuates the negative effects of partial sleep deprivation on cognitive and short-term maximal performance: Effect of time of day. (3rd July 2021) - Khemila, Syrine; Abedelmalek, Salma; Romdhani, Mohamed; Souissi, Amine; Chtourou, Hamdi; Souissi, Nizar
ABSTRACT: This study assessed the effect of time of day (TOD) and listening to music during warm-up on cognitive and physical performances after partial sleep deprivation (PSD) and normal sleep nights (NSN). In a randomized order, twelve male physical education students [mean (SD) age 20.3 ± 2.0 y; BMI 22.90 ± 3.57 kg/m 2 )] completed a 30-s Wingate test ( i.e ., mean (MP) and peak powers (PP)), simple (SRT) and choice reaction times (CRT), a mental rotation test (MRT) and a selective attention test. Measurements were performed at 07:00 h and 17:00 h after a NSN and PSD with and without music, with an in-between recovery period of ≥72. Salivary cortisol was measured before and immediately after the Wingate test. Compared to NSN, the results showed that PSD decreased PP ( p < .05, d = 0.86) and MP ( p < .01, d = 0.86) in the afternoon. However, compared to NSN, listening to music during the warm up after PSD enhanced PP ( p < .01, d = 1.40) and MP ( p < .05, d = 0.82) in the morning and PP ( p < .05, d = 0.78) in the afternoon. Moreover, listening to music lowered post-exercise cortisol in the morning both after NSN ( p < .05, d = 0.79) and PSD ( p < .05, d = 0.11). After PSD, music reduced the negative mood states ( p < .01, d = 0.94), the SRT ( p < .05, d = 0.79) and the CRT ( p < .05, d = 0.49) in the afternoon. These findings suggest that listening to music during warm-up (i) enhances cognitive and short-term all out performances after NSN and PSD and (ii) partially counteracts sleep-loss-induced degradation of physical and cognitive performances at both TODs.